Making universal health care effective in Argentina: A blueprint for reform - Rubinstein, Adolfo Luis (2018)
The reform of a health care system requires attention to specific components but also to the creation of an environment that supports change. Argentina has achieved nominal universal health coverage (UHC) but it still needs to work on achieving effective universal health coverage, especially with regard to quality and equity. Nominal coverage means that everyone has been enrolled and has the right to access, and effective coverage means that people have actually received prioritized health care services. In this article, we present our proposals to advance UHC in Argentina. The article includes an overview of Argentina’s health system, then introduces the driving forces for reform, and finally analyzes four key issues where we provide our action plan to implement health reform for moving Argentina forward. Overall, our ultimate goal is to provide actual UHC and not aspirational UHC in Argentina by strengthening provincial health systems through enforcing public insurance schemes; utilizing an explicit priority-setting approach to make decisions on health coverage; reducing health disparities in coverage and outcomes, at least on prioritized health problems; and building a primary care–oriented health care system.